Massive serpentinite carbonation at Linnajavri, N-Norway - Beinlich, Andreas; Plümper, O.; Hövelmann, J.; Austrheim, H.; Jamtveit, B. (2012)
Carbonation of ultramafic rocks is being considered as an in situ disposal strategy for anthropogenic CO 2. We present observations from massively carbonated serpentinites at Linnajavri, N-Norway, where serpentinized fragments of the dismembered ophiolite are hydrothermally altered to soapstone and listvenite on a km-scale. Several sharp reaction fronts between the soapstone and the serpentinite can be followed for hundreds of metres. Listvenite is present between the underlying carbonate-mica schist and the soapstone. The O-isotopic compositions of vein minerals in the listvenite and adjacent soapstone indicate an isothermal formation at ~275°C. In agreement with C-isotope signatures, field observations suggest that fluids were derived from overthrusted sediments. Porosimetry data, mass-balance calculations and the perpetuation of serpentinite structures imply an isovolumetric alteration. We conclude that the reactions stopped due to the cessation of the external CO 2 supply. Soapstone formation is associated with sequestration of more than 13 Mt of CO 2. © 2012 Blackwell Publishing Ltd.